Corporate social responsibility of hotels in Bali – Indonesia: practices, drivers and barriers - Luh Putu Mahyuni (Curtin University, 2016)
Guided by the theory of planned behaviour (Ajzen 1991), this thesis investigates CSR Practices (CSRP) and factors that explain CSRP of hotels in Bali – Indonesia. A mixed methods approach is used. The findings of this thesis indicate that CSRP of most local hotels are less advanced. Hotel managers are influenced more by external forces than internal factors in making CSR decisions. The owners and certification organisations play a significant role in shaping CSRP.